Keberlanjutan Agro Edu Wisata Organik (AEWO) Mulyaharja Kecamatan Bogor Selatan Kota Bogor - Ghifari, Faris; Djuwendah, Endah; Rochdiani, Dini; Qanti, Sara Ratna (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Agro Edu Wisata Organik (AEWO) Mulyaharja is the only tourist village in Bogor City that falls into the category of an advanced tourist village. However, in recent years, the number of visitors to AEWO Mulyaharja has been decreasing annually, which is one of the indicators that the development of AEWO Mulyaharja has not been optimal. This research aims to determine the sustainability level of AEWO Mulyaharja and analyze the sensitive factors affecting the sustainability of AEWO Mulyaharja. The design of this research uses quantitative approaches, with the survey method employed for data collection. The analysis tools used the Multidimensional Scaling method in the RAP-Tourism technique. The analysis results show that overall, the sustainability levels of the economic and socio-cultural dimensions are quite sustainable, while the ecological and technological dimensions are categorized as highly sustainable. The sensitive attributes that most significantly influence the sustainability of AEWO Mulyaharja in a multidimensional manner are the presence of local attractions and traditions, the existence of historical sites or artifacts at the tourist location, and safety.